Development Arduino Data Logger using TDR H3CR for Tidal Simulator - Kusuma, Hollanda Arief; Putra, Riandra; Suhendra, Tonny (Jurnal Teknologi Elektro, 2024)
Tides are the rise and fall of sea level repeatedly over a certain period of time. Tides have an important role in life, such as in the aspects of tourism, fisheries, economy, shipping, and student research. Learning media innovation develops until it looks real, which is called a simulation or simulator application. Simulator media as learning has many benefits, such as shortening research time and reducing research funds. Raja Ali Haji Maritime University has a tidal simulation model that has been equipped with a floodgate, and the weakness of the simulator is that it still uses a manual system. Researchers developed a new tidal simulation tool without a generator and only analyzed the up and down data that had been set using H3CR, DC Water Pump, and DC Selenoid Valve as a tool for automatic tidal circulation commands.